(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Integrated Child Development Services (ICDS) system, initiated by the Government of India for early childhood care and creation, is a special, robust and the world’s largest network. It aims to improve children’s survival and all-round growth, especially for the poorer and most disadvantaged parts of society. For infants, pregnant women, nursing mothers and teenage girls, the ICDS scheme initiated in 1975 is discussed in near collaboration with health facilities to enhance the health condition and overall welfare of children and other beneficiaries. It delivers an interconnected bundle of six programmes, since the usefulness of a given programme relies on the assistance it gets from the linked programmes. The ICDS has grown dramatically in its reach and reach over the years after its conception in 1975, and is still one of the greatest and most special needs of a child in the world. Since the inception of the ICDS project in 1975, three phases of expansion have been carried out from time to time throughout the world.